Suplementação com melaço de soja na dieta de ovinos: parâmetros sanguíneos, consumo, digestibilidade e comportamento ingestivo - Paula, Carina Gonçalves de (2015)
This study includes two experiments, and in the first the goal was to evaluate biochemical and hematological parameters in sheep supplemented with different soybean molasses levels in the diet. Serum levels of protein, phosphorus and calcium/phosphorus showed significant differences in relation to the assessed days. Uric acid and aspartate aminotransferase (AST) levels showed significant changes for the treatments. Energy parameters were not altered for days and for treatments. Hematological variables were similar for all parameters studied. Supplementation with soy molasses can interfere on levels of uric acid and AST, not causing metabolic changes in the evaluated parameters. In the second experiment the goal was to evaluate the intake and digestibility of nutrients, ingestive behavior and performance of sheep supplemented with different soy molasses levels in the diet. The protein intake relative to body weight and protein consumption and mineral matter were significant for the treatments. The apparent digestibility of nutrients had no change, as well as ingestive behavior, intake efficiency, rumination and chewing and rumination frequency. The water consumption and water/molasses consumption ratio were significantly different for the treatments. Supplementation with up to 12% soy molasses does not change dry matter intake, digestibility of nutrients and ingestive behavior of sheep, but increased consumption of protein and mineral matter. Then, it is an alternative of supplementation in the diet.